The Relationship Between Mental Toughness and Sports Motivation With The Achievements of Introvert and Extrovert Personality Athletes in Individual Sports - Berliana, Agiarnanda Wafiq; Junaidi, Said; Kusuma, Donny Wira Yudha (Journal of Physical Education and Sports, 2023)
The researcher's observations during fieldwork found that coaches in Semarang City pay insufficient attention to the psychological aspects of their athletes during training or competitions. This includes aspects such as mental toughness and sports motivation, which may be related to the performance of introverted and extroverted athletes. The aim of this research is to determine the significant differences in the relationship between mental toughness and sports motivation with the performance of introverted and extroverted athletes in individual sports. The research method employed is quantitative with a correlational approach. The sample size consists of 11 introverted athletes and 35 extroverted athletes. Prerequisite analysis includes tests for normality, linearity, and multicollinearity. Hypothesis testing involves multiple linear regression, simultaneous test (F), partial test (t-test), and coefficient of determination. The results indicate that mental toughness and sports motivation variables have a significant relationship with the performance of introverted athletes. The contribution of mental toughness and sports motivation variables to influencing the performance of introverted athletes in individual sports is 48.6%. However, these variables show an insignificant relationship with the performance of extroverted athletes, with a contribution of 9.2% in individual sports.